Fog of war [videorecording (DVD)] - Langsdale, Luke; Cusack, John; Sorvino, Mira; Rohrig, Geza; Hildebrand, Brianna; Able, Jake (Decal Releasing, LLC, 2025)
With WWI raging around them, an injured pilot and his fiancee find themselves stranded on a remote estate. As the Allies plan the D-Day Invasion, the couple become aware of a Nazi spy hiding amongst them with stolen documents bound for Germany. Unsure of who to trust, and facing danger around every corner, they must uncover the spy's identity as the outcome of the war hangs in the balance.